An Analysis of Students’ Errors in Translating Indonesia-English Narrative Text - Marlin Margaretha Manu; Anggelina Martina Nahak (IJLHE: International Journal of Language, Humanities, and Education, 2024)
This study aims to determine the types of errors in translating narrative texts from Indonesian to English and the most dominant types of errors in translating narrative texts from Indonesian to English by students of class X IPA 1 SMA Negeri 4 Kota Kupang. This research uses descriptive qualitative research. The subjects of this study were 15 students of class X IPA 1. The data source was taken from translating students' narrative texts from Indonesian into English. The research instrument is a translation task. The translation task was used to obtain data about student errors in Indonesian to English translation texts. The findings of this study indicate that there are four types of translation errors, namely: Omission, ex: SL: Then the dog arrived, SL: The dog arrived, Correct: Then the dog arrived. In addition, ex : SL: Cat and fox, TL: Cat and fox, Correct: Cat and fox. Mis formation, ex: SL: A moment later, TL: Just then, Correct: A moment later. Mis ordering, ex: SL: At least I know, TL: At least I know, Correct: At least I know. Moreover, the most dominant types of translation errors, the researcher concluded that the students' problems in translating narrative texts from Indonesian to English were mostly formation errors of 120 errors. Mis formation is the most dominant type carried out by students of class X IPA 1 SMA Negeri 4 Kota Kupang. Suggestions for improving the teaching and learning process, especially in the teaching and learning process of translation as one of the subjects in class X IPA 1 SMA Negeri 4 Kota Kupang, students must practice translating Indonesian texts into English or vice versa in class or outside of class to improve their translation skills.